Lugares de bruma: coordenadas do imaginário narrativo de Murilo Rubião - Cleber Araujo Cabral (2011)
This work consists in an exploratory reading of Murilo Rubiãos short stories, whereof a surveying of the space, time and person fictional images that conform his narrative imaginary. We look for how a perception of reality, sugested by Murilos literary view, occurs by the way of the destabilization of spatial-temporal references, that oscilates between the archaic and the modern, configuring, thereby, a fictional reality ruled by an logic of uncertainty. For both, are used as reading operators the concept of chronotope, formulated by Mikhail Bakhtin, and the notion of heterotopy/heterotopology, purposed by Michel Foucault. Like theorical landmarks, we dialogue with Italo Calvinos appointments about reality and fiction, reflections of many authors about the ways of approaching space, time and person categories in the literary text scope and the Wolfgang Isers speculations about the relations between the fictive and the imaginary instances in the production of the reality present in fiction text.